Sistema informático para el control administrativo de la farmacia tres Hermanos ubicada en el cantón Quevedo - Fernández Rendón, Joffre Rolando (2015)
This paper is designed to carry administrative control of the three brothers pharmacy located in Canton Quevedo; to be intended to carry out a computer system for administrative control, gaining more control and profit, helping to have all the requirements and information as are requested product, billing, product in stock, employee information, information products and customers. With the respective and appropriate management. It should be noted that the achievement of this system we have focused on the Scrum methodology; since it is a process that is applied regularly a set of good practice collaboratively in equipment and get the best possible result in a highly productive project. In addition we have aligned according to the IEEE -830 standard; writing software specifications that indicate exactly what the customer wants further allowing the provider to understand exactly what the customer requires. The technology used in this system is very important and widely used in the middle of the programming; using the language .Net 2010 in conjunction with crystal report To ensure the safety and availability of the data management system based on MS SQL Server 2012, the same that has an excellent architecture and robustness in electronic data processing was used. After reaching our goal in creating the system we can give us realize the importance of it; and it is helpful for pharmacy three brothers which reduces unnecessary spending on logistics materials and human effort.